Computerized application for analysing the time and instructional parameters in sport coaching and physical education teaching - Viciana, J.; Fdez-Revelles, A. B.; Zabala, M.; Requena, B.; Lozano, L. (International Journal of Computer Science in Sport, 2002)
A software made in Visual Basic® is presented here, attending two important competencies in the first formation of any preservice Physical Education (PE) teacher or any sport coach: 1) time management available to develop the contents in a school or in the training sessions, and 2) feedback administration for both students and athletes.